Pendampingan Promosi Media Sosial dan Kesehatan Kerja pada UMKM Kerajinan Rotan - Merita Arini; Harumi Iring Primastuti; Rizkan Triatmaja; Erviani Yanura Trisna Wijayasari; Danis Noorveby Rachmawati; Vicky Ramadhanu (Ilin Institute, 2022)
Tujuan dari pengabdian masyarakat ini adalah untuk meningkatkan pengetahuan dan keterampilan mengenai pemasaran produk melalui media sosial dan pertolongan pertama pada kecelakaan kerja. Pengabdian masyarakat yang dilakukan menggunakan pendekatan action research di mana mitra terlibat dalam menentukan masalah prioritas yang dipecahkan serta bagaimana cara memecahkannya. Pengabdian dilakukan melalui program pendampingan dan pelatihan fotografi dasar, pengelolaan Instagram sebagai media promosi, serta pelatihan perawatan luka sayat sesuai risiko bidang pekerjaan. Didapatkan hasil tercapainya indikator: (1) mitra mengetahui teknik fotografi produk dasar, pemasaran online melalui Instagram, dan memiliki akun Instagram; serta (2) terampil melakukan perawatan luka. Pelatihan yang dilakukan dinyatakan bermanfaat bagi mitra untuk meningkatkan pemasaran melalui media sosial dan keterampilan dalam kesehatan kerja. Hasil pelatihan diharapkan dapat terus diterapkan untuk meningkatkan penjualan dan menjaga produktivitas mitra. Abstract. Behavior customer shifting and technology require changes in the methods of marketing of creative industrial products. Furthermore, occupational safety and health are crucial to maintaining worker productivity. The situation of Micro, Small, and Medium Enterprises partner for rattan handicrafts in Sendangarum Village, Minggir, Sleman, Yogyakarta Special Region was that marketing was still conventional and unfamiliar with occupational safety and health. This community service aims to increase knowledge and skills regarding product marketing through social media and first aid in work accidents. Community service was carried out using an action research approach where partners were involved in determining priority problems to be solved and how to solve them. Thi community service was carried out through mentoring programs and basic photography training, managing Instagram as a promotional medium, and training in wound care according to the risks of the field of work. The results of the achievement of indicators: (1) partners know and can conduct basic product photography techniques, online marketing through Instagram, and have an Instagram account; and (2) skilled in wound care. The training carried out is beneficial for partners to improve marketing through social media and skills in occupational health. The training results are expected to continue to be applied in increasing sales and maintaining partner productivity.